Capturing the Reverberations of the 1965–66 Killings in the Balinese Landscape: The Artistic Work of Leyla Stevens - Hearman, Vannessa (SEAP Cornell, 2023)
This article examines the work of Australian-Balinese artist, Leyla Stevens in reworking and re-presenting aspects of the Balinese experience of the 1965-66 killings. In her award-winning work, Dua Dunia (two worlds), the diasporic artist demonstrates the persistence of memory and the indispensability of 'talk' in recounting the story of a place that is not recorded in official histories. By using a dialogue created between two women speaking of the Balinese landscape and its relationship with history, performed in a kidung, a poem recited in song, Stevens suggests that the oral transmission of history, no matter how faltering, can open up new ways of remembering. In this way, she highlights the vital contribution of local communities in reconstructing and transmitting memories of violence, on one hand, and, on the other, the role of nature and landscape as sentinels of memory. Titling her work Dua Dunia refers to her diasporic status on one hand, but also to the haunting of those whose lives are marked by encounters with spirits who refuse to leave sites of violence, who 'walk in two worlds.' The article examines finally how the reception of her work can be a measure of the contribution of artists to understanding the 1965-66 killings outside Indonesia.